Effects of Trichoderma Harzianum and Fusarium Solani Inoculant on the Resin Content of Agarwood (Gyrinops Versteegii (Gilg.) Domke) - Mega, I Made; Kartini, Ni Luh; Innosensia, Ni Luh Putu Citra (International Journal of Biosciences and Biotechnology; Vol 10 No 2 (2023): INTERNATIONAL JOURNAL OF BIOSCIENCES AND BIOTECHNOLOGYDO - 10.24843/IJBB.2022.v10.i02.p01, 2023)
This study aimed to determine which fungal inoculants, Trichoderma harzianum or Fusarium solani in a solid or liquid form, produced the highest resin content in agarwood trees. This experimental study used a randomized completely block design (RCBD) with seven treatments in triplicates: solid Trichoderma harzianum inoculants in pellets(A) and capsules (B), liquid T. harzianum inoculants (C), solid Fusarium solani inoculants in pellets (D) and capsules (E), liquid F. solani inoculants (F), and control or without inoculants (G). Parameters observed were the color and aroma of the infected agarwood and the resin content of the harvested sapwood. Quantitative data obtained from observations/measurements were analyzed statistically with analysis of variance and a subsequent LSD test at a 5% significance level following a significant result. The results showed that treatments using different fungal inoculants had no significant effects on the resin content of agarwood. However, inoculants in pellets and capsules tended to increase the resin content. The resin content of agarwood ranged from 15.97% to 21.53%, and the highest level was obtained from treatment A (solid T. harzianum inoculants in a pellet form)